Analisis Tentang Pemahaman Pajak E-Commerce Pada Pemilik Bisnis Online Sebagai Upaya Kepatuhan Pajak Di Kota Bekasi (Studi Kasus Pada Kpp Pondok Gede) - Alfian Wicaksono; Ratih Kumala (Jurnal Ilmu Administrasi Publik, 2023)
The phenomenon in this study is the lack of understanding of online business owners regarding e-commerce taxes originating from their business of buying and selling transactions in the digital world, having barriers to socialization for e-commerce taxes, many do not understand their rights and obligations as mandatory taxes, the low trust of taxpayers in the government because they do not feel directly the rewards of the money they pay for the taxes themselves so that there is a perception that the taxes they pay will definitely be misused. The purpose of this study is to see how and to what extent the level of understanding of online business taxpayers at KPP Pratama Pondok Gede regarding ecommerce taxes as an effort to comply with taxes, obstacles from taxpayers and KPP Pratama Pondok Gede, as well as efforts made by taxpayers and KPP Pratama Pondok Gede to increase understanding of their tax obligations. This research uses descriptive research with a qualitative approach. The analytical method used is the Qualitative Data Analysis Method. The results of this study indicate that tax understandinge-commerceonline business owners who are registered at KPP Pratama Pondok Gede are still not optimal, when viewed from the realization of revenue in 2021 they have not been able to reach the target with a percentage of 99.27%. Even though in 2021 the realization of tax revenue has increased from the previous year, it has not been able to reach the predetermined target, in this case KPP Pratama Pondok Gede has human resource constraints, so various efforts have been made to overcome these obstacles, one of which is providing consultation on the Account Representative and Helpdesk at the Pondok Gede KPP Pratama service office.